THE EFFECT OF SELF-EFFICACY AND FINANCIAL LITERACY ON ENTREPRENEURIAL INTEREST OF ECONOMIC EDUCATION STUDENTS - Ramadan, Putri Syahrani (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to analyze the effect of self-efficacy (X1) and financial literacy (X2) on entrepreneurial interest (Y) among 2021 cohort students of the Economic Education Study Program at Universitas Panca Sakti Bekasi. The research used a quantitative approach with a survey method involving 56 respondents selected from a population of 127 students using the Slovin formula with a 10 percent margin of error. The research instrument was a questionnaire tested for validity and reliability. Data were analyzed using multiple linear regression to determine partial and simultaneous effects. The results indicate that self-efficacy (X1) does not have a significant partial effect on entrepreneurial interest (Y), while financial literacy (X2) has a significant partial effect. Simultaneously, both variables significantly affect entrepreneurial interest (Y) with a contribution of 53.1 percent. These findings emphasize the importance of improving students’ financial literacy to enhance their entrepreneurial interest.